Reconstruction of a Traumatic Large Upper Eyelid Avulsion with Tarsoconjunctival Graft and Rotational Flap: A Surgeon’s Preference - Muhammad Fariz; Sutjipto (Universitas Airlangga, 2023)
Introduction: Large, full-thickness upper eyelid defects management presents a thorough and challenging approach due to the multilaminar character of the eyelid and its dynamic function. The Cutler-Beard flap method has been the mainstay management, but posterior lamellar graft usage with recent modifications may reduce complications. Case Presentation: A 43-year-old man presented to the emergency ward after a traffic accident left him with a full-thickness laceration on his left upper eyelid and an approximately 60% avulsion on the one-third medial of the eyelid. Traumatic ptosis was also found. After considering the large size of the affected area and the probability of faster wound healing, a free graft from the tarsus and conjunctival eyelid of his fellow eye was harvested to replace the posterior lamellar of the affected eye and closed the defect with a rotational skin flap from the remaining of the left upper eyelid. Conclusions: This technique could be one of the alternatives to the more common cutler-beard flap with mild complications. However, temporary visual obstruction cannot be avoided due to the traumatic ptosis complication of this patient.